Code-Switching Patterns Among Young Adults in Pakistan: A Comparative Study of Punjabi-English and Pashto-English Bilingualism in Informal Settings - Nida Kainat; Maryam Maheen Moon; Shehzadi Gull (`, 2025)
The study examines the repertoires of code-switching by young bilingual adults in Pakistan with reference to Punjab-English speakers in Rawalpindi, and the Punjab and Pashto-English speakers in Kohat. The research will also be conducted with the aim of explaining the mechanisms and reasons of the interchange of language by bilingual people in different kinds of informal communication, and which social, educational and regional factors define language behavior. Information gathered was done using informal recording of conversations and short interviews of university going youth in both cities. The results of the analysis show that the Punjabi-English bilinguals are more prone to the intra-sentential switching where English words and phrases are used in the Punjabi sentences with ease. Pashto-English bilinguals on the other hand use inter-sentential switching phenomena mostly switching languages between the sentences especially in academic or peer related discussions. The results point to the fact that being urbanized, the influence of the media and the educational level highly influence the preferences and rate of code-switching. Furthermore, the attitude of participants to code-switching was rather positive and corresponds to adaptive bilingualism in everyday situations. Nevertheless, the Pashto language speakers were found to be more conservative in its usage, particularly, in formal or elder-oriented contexts. Besides bringing in the sociolinguistic insights to bilingual speech in Pakistan, this paper has also pointed out the importance of regional identity in language practices of the young people. The comparison aspect offers a better understanding of how different bilingual communities bargain in their language use in the domain of cultures and social aspects. Keywords: Code switching, bilingualism, Punjabi English, Pashtun English, Sociolinguistics, language attitudes, youth communications, dialects, Pakistan